One-step synthesis of C quantum dots/C doped g-C3N4 photocatalysts for visible-light-driven H2 production from water splitting. (3rd November 2022) - Cao, Jian; Jin, Xiaoli; Ma, Zhaoyu; Wang, Huiqing; Xu, Yixue; Guo, Yuwei; Xie, Haiquan; Zhang, Junying
Abstract: Graphitic carbon nitride (g-C3 N4 ) is gaining more and more attentions as a promising metal-free photocatalyst for H2 production. Nevertheless, from the perspective of practical applications, the photocatalytic performance over g-C3 N4 in visible-light region needs a further improvement. In this work, C doping and C quantum dots (QDs) are co-integrated in g-C3 N4 by a one-step thermal polymerization method to obtain an advanced C QDs/C doped g-C3 N4 photocatalyst. The synergistic effects of C doping and C QDs modification promote the photocatalytic activity of g-C3 N4 significantly. The optimal C QDs/C doped g-C3 N4 exhibits a significant improvement on visible-light-driven photocatalytic hydrogen production (205 μ mol g −1 h −1 ) with an apparent quantum yield (AQE) at 420 nm reaching 1.24%, which is approximately nine-fold enhancement than that of pristine g-C3 N4 . The increased photocatalytic activity mainly benefits from the enhanced visible light absorption and carrier separation efficiency. This study may open a new perspective for the design and fabrication of C-modified g-C3 N4 for photocatalytic hydrogen production.